Salivary Aldehyde Dehydrogenase: Activity towards Aromatic Aldehydes and Comparison with Recombinant ALDH3A1 - Giebułtowicz, Joanna (Molecules, 2009)
A series of aromatic aldehydes was examined as substrates for salivary aldehyde dehydrogenase (sALDH) and the recombinant ALDH3A1. Para-substituted benzaldehydes, cinnamic aldehyde and 2-naphthaldehydes were found to be excellent substrates, and kinetic parameters for both salivary and recombinant ALDH were nearly identical. It was demonstrated that for the fluorogenic naphthaldehydes the only produced reaction product after incubation in saliva is the carboxylate.